1991
DOI: 10.2337/diacare.14.5.386
|View full text |Cite
|
Sign up to set email alerts
|

Role of Height and Glycosylated Hemoglobin in Abnormal Nerve Conduction in Pediatric Patients With Type I Diabetes Mellitus After 4–9 yr of Disease

Abstract: Prospective evaluation of nerve conduction parameters in pediatric patients with diabetes should include both height (the most significant independent variable in latency analysis) and mean glycemic control (the most consistent variable in velocity analyses) as variables in the assessment of the natural history of evolving peripheral neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
25
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 11 publications
7
25
1
Order By: Relevance
“…Sensory nerve conduction (SCV and SNAP) was less often affected. This distribution is similar to the one found in adult patients with diabetic neuropathy [8,33,34] and in children with IDDM [16,21]. Earlier studies in adults with overt diabetic neuropa-L. Hyllienmark et al: Subclinical nerve dysfunction thy have suggested that sensory nerve fibres are affected before motor fibres [33,35].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Sensory nerve conduction (SCV and SNAP) was less often affected. This distribution is similar to the one found in adult patients with diabetic neuropathy [8,33,34] and in children with IDDM [16,21]. Earlier studies in adults with overt diabetic neuropa-L. Hyllienmark et al: Subclinical nerve dysfunction thy have suggested that sensory nerve fibres are affected before motor fibres [33,35].…”
Section: Discussionsupporting
confidence: 60%
“…It is noteworthy that only 3 of the 75 patients had any signs or symptoms of neuropathy. A decrease in both MCV and SCV has previously been demonstrated in children and adolescents with IDDM [14,16,21]. However, this is the first study in which all patients have received MIT-treatment.…”
Section: Discussionmentioning
confidence: 84%
“…Puberty is likely to be one of the most critical periods for the development of peripheral nerve dysfunction in patients with type 1 diabetes because of various hormonal changes affecting glycemic control during puberty (8). The Tanner stages of pubertal maturation (9) have rarely been considered in studies on peripheral polyneuropathy in young patients with type 1 diabetes (4,10), and there is a need for additional knowledge of the role of puberty in the development of such abnormalities. The purpose of this cross-sectional study was to assess clinically and neurophysiologically the signs of damage to the peripheral nerve system observed in a large series of adolescent patients with type 1 diabetes in relation to pubertal maturation.…”
mentioning
confidence: 99%
“…Poor metabolic control has a negative impact on NCV and on nerve amplitude (4) and is an independent risk factor for symmetric distal DP (7). Puberty is likely to be one of the most critical periods for the development of peripheral nerve dysfunction in patients with type 1 diabetes because of various hormonal changes affecting glycemic control during puberty (8).…”
mentioning
confidence: 99%
“…Studies using objective measures of nerve dysfunction (eg, nerve conduction studies [NCS]) demonstrated abnormalities in 28% to 58% of children with diabetes [1][2][3][4] and categorized them as high risk for developing severe secondary complications such as foot ulcerations. 5 These severe complications can only be averted when signs of the disease are detected early.…”
mentioning
confidence: 99%